Effects of a New Herbal Formula and Low-Intensity Electromagnetic Radiation of Ultrahigh Frequencies in Obesity and Metabolic Syndrome: an Experimental Study - Zhanna V. Dzampaeva; Fatima S. Datieva; Elena A. Takoeva; Marina I. Nartikoeva (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
INTRODUCTION. The high prevalence of metabolic syndrome (MS) is becoming a serious problem for the entire world. AIM. Experimental evaluation of metabolic syndrome-induced changes in the microcirculation, kidney structure, serum biochemistry, the stress resistance of rats and the possibility of their correction with complex phytoadaptogens (CPhA) and low-intensity extremelyhigh-frequency electromagnetic radiation (EHF EMR) and their combination. MATERIAL AND METHODS. The experiment was performed on 40 male Wistar rats (body mass 330±20 g), divided into 4 groups: Group1 - control, Group 2 - metabolic syndrome (MS), Group 3 - treatment of metabolic syndrome with complex phytoadaptogens (CPhA), Group 4 - treatment with CPhA and EHF EMR. In Groups 2, 3, 4, the animals received a high-carbohydrate, high-fat diet for 16 weeks. The CPhA of official 70% tincture of Glycyrrhiza glabra and 40% tincture of Rhodiola rosea, Acantopanax senticosus in a ratio of 1:2:1. Group 3 animals were administered CPhA for 14 days with drinking water after 16 weeks on the diet. RESULTS AND DISCUSSION. The study in question showed that a combined application of CPhA and EHF EMR has systemic effects on the nervous, endocrine, immune systems with changes in the content or synthesis of biologically active substances (hormones,cytokines, neurotransmitters) playing an essential role in the regulatory mechanisms of blood microcirculation. It is a very important aspect for the treatment of metabolic syndrome (MS), with endothelial dysfunction being the key pathophysiological element. CONCLUSION. Phytoadaptogens are promising drugs for the treatment of MS, especially in combination with EHF EMR, since their effects potentiate each other. CPhA affect the etiology and pathogenesis of metabolic syndrome through several mechanisms; therefore, they are promising medicines in the complex fight against excess weight.